Innovations in Maternal-Fetal Medicine and Neonatology: A Multidisciplinary Approach to Enhancing Care for High-Risk Pregnancies and Premature Infants - Albar, OHUD Hamed; Maghfuri, Lulah Mohammed Hassan; Alhadri, Hussain Yahya Sokai; ALBAHLI, FAHAD HAMOUD FAHAD; Omairah, Mohammed Hams Muqahm Bin; Albahli , Hamoud Mohammed Hamoud; Alswilm , Fryal Abdulaziz; Alotibi , Faleh Sanhat Sant; Aloteiby, Fares Nasser; Alonaydheel, Nouf Hikman Nasser; Al-Mutairi, Mohammed Mutab; ALHARBI, MAJED MANSOUR MANSOUR; et al. (Journal of Ecohumanism, 2024)
Background: Maternal-fetal medicine and neonatology are pivotal fields in managing high-risk pregnancies and premature infants. Recent innovations in these areas emphasize the importance of a multidisciplinary approach to improve outcomes for vulnerable populations, particularly concerning brain health throughout the life course. Methods: This review synthesizes recent literature on the advancements in maternal-fetal medicine and neonatology, focusing on methodologies and strategies that enhance care for high-risk pregnancies and premature infants. A comprehensive search was conducted across several databases, including PubMed, Scopus, and MEDLINE, targeting studies published from 2018 to 2023. Results: The findings indicate that integrating fetal-neonatal neurology (FNN) into clinical practice significantly enhances the precision of diagnostics and interventions. The application of a life-course exposome perspective reveals that early exposures can have lasting impacts on brain health, necessitating early identification and intervention strategies. Furthermore, studies highlight the need for specialized training in FNN to equip healthcare professionals with the skills necessary to address the complexities of prenatal and neonatal care. Conclusion: Innovations in maternal-fetal medicine and neonatology underscore the importance of a collaborative, interdisciplinary approach to managing high-risk pregnancies and caring for premature infants. There is a pressing need for educational programs that incorporate FNN principles, ensuring that healthcare providers are adequately prepared to optimize outcomes for mothers and their children. Future research should focus on expanding these educational frameworks and assessing their impact on clinical practice